Indonesian Public Diplomacy in Holding the 2022 Moto GP to Improve Indonesia's Nation Brand After the Covid-19 Pandemic - Kena, Siti Rukia; Priadarsini, Ni Wayan Rainy; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This research aims to describe Indonesia's public diplomacy strategy through holding the 2022 Moto GP to improve Indonesia's nation brand after the pandemic Covid-19. This research uses descriptive- qualitative methods with primary data sources that obtained from reports and documents from the Indonesian government and secondary data sources from various literatures that related to the research topic. The Covid-19 pandemic has had an impact on the image of Indonesia. Indonesia is considered a country with poor handling of Covid-19, so many countries are limiting visits to Indonesia. Of course this will affect Indonesia's image as a tourism country.Therefore, Indonesia is trying to overcome this problem by taking advantage of the momentum of holding the 2022 Moto GP in Mandalika. Indonesia uses public diplomacy in holding international racing events to enhance Indonesia's image as a tourism country that is comfortable and safe from Covid-19. The results of this study show that the efforts made by the government in holding the Moto GP 2022 have succeeded in increasing Indonesia's nation brand even though it has not been optimal. The researcher uses the public diplomacy concept to explain the efforts made by Indonesia and the nation brand concept to see the effect of public diplomacy on Indonesia's image. Keywords : Indonesia, Moto GP 2022, Nation Brand, Pandemic Covid-19, Public Diplomacy